Self Medication Practices among Patients seen in A Suburban Tertiary Eye Care Centre in Nigeria - Ajayi, Iyiade A; Omotoye, Olusola J; Ajite, Kayode O; Fadamiro, Christianah O; Ajayi, Ebenezer A (Asian Journal of Medical Sciences, 2013)
Objective: To identify practice and pattern of self-medication use among new patients in ophthalmology clinic in a suburban community. Background: Self medication is a common practice all over the world. When consumers self-medicate without first consulting the eye care giver, issues of safety and inappropriateness of use arise. Methods: A cross sectional, analytic and questionnaire based study of 470 consecutive patients seen between April and June 2011 in a tertiary eye care centre in Nigeria was conducted. Data were analyzed using SPSS and p value <0.05 was considered significant. Results: The mean age was 43 ±24 years with a M: F ratio of 1:1.3. There was utilization of an initial medication in 73.6% (346) of the respondents before presentation. Of the group that utilized medication, 108(31.3%) could neither mention name nor show sample of medication used. Only 14.9% of patients consuming nonprescription drugs sought assistance from any health professional regarding proper selection or use. Majority (73.6%) of the patients got their medication following assistance sought from retail outlets of non-prescription medicine, friends, relations or self prescription. The utilized medications were inappropriate in 90% of the respondents who utilized them. The most common symptoms necessitating the utilization of initial medication were blurring of vision and itching. Conclusion: There was a high rate of self medication with blurring of vision and itching as the commonest complaints among the patients. There is still a very low incidence of preventive eye care in terms of ophthalmic check-up among our people. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8452 Asian Journal of Medical Science, Volume-5(2) 2014: 85-90